Actein antagonizes colorectal cancer through blocking PI3K/Akt pathways by downregulating IMPDH2. Issue 8 (September 2021) - Yan, Liwei; Wang, Dandan; Liu, Xiaoming; Gu, Chao; Gao, Shanyu
Abstract : Actein, a triterpene glycoside, isolated from rhizomes of Cimicifuga foetida, was reported to exhibit anticancer effects in vitro and in vivo . However, the effects of actein on colorectal cancer (CRC) remains unclear. As one of the most popular cancers all over the world, CRC ranked third place in both men and women. Recently, we investigated the potential anti-CRC effects of actein and its mechanisms. The Cell counting kit-8 cell proliferation assays, cell cycle detection, apoptosis detection, reactive oxygen species and mitochondrial membrane potential evaluation, western blot, as well as SW480 xenograft mice model were conducted to illustrate the mechanisms of action on anti-CRC effects of actein. Actein could significantly inhibit the human CRC cell lines SW480 and HT-29 proliferation, whereas less antiproliferation effects were found in normal colorectal cell lines HCoEpiC and FHC. Administration of actein resulted in G1 phase cell cycle arrest in both SW480 and HT-29 cells. Moreover, mitochondria-mediated apoptosis was also observed after treatment with actein in SW480 and HT-29 cell lines. Further investigation of mechanisms of action on actein-mediated anti-CRC proliferation effects indicated that the phosphoinositide 3-kinases (PI3K)/Akt pathways were involved. Actein significantly downregulated the phosphorylation of key molecules in PI3K/Akt pathways, including mTOR, glycogen synthesis kinase 3β (GSK-3β), as well as FOXO1. In addition, inosine 5′-monophosphate dehydrogenase type II (IMPDH2) was also observed decreasing in both SW480 and HT-29 cell lines after actein treatment, suggesting that actein may inhibit the PI3K/Akt pathways by decreasing IMPDH2. Finally, our SW480 xenograft model verified the anti-CRC effects and the safety of actein in vivo . Our findings suggest actein is worthy of further investigation as a novel drug candidate for the treatment of CRC.